Predictors of hepatorenal syndrome in patient with decompensated liver cirrhosis - Karki, Sanjit; Shrestha, Roshan; Shah, Manoj; Shrestha, Ramila; Paudel, Bidhan Nidhi (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Hepatorenal syndrome (HRS) is one of the severe complications of decompensated liver cirrhosis which has poor outcome. Predictive models are important aspect in assessment of high risk patient. Method: This prospective analytical study was conducted in Gastroenterology unit of Bir hospital from December 2018 to April 2020. Seventy patient of liver cirrhosis with ascites (CTP score 7 or more) were followed for a period of three months. The outcome of study was hepatorenal syndrome. Predictors were assessed from baseline variables. Result: Total 65 patients completed the study. The mean age of study population was 47.38 ±11.38 years and 52(80%) were male. The most common aetiology was alcohol 55(84 %). Eight (12.5%) developed HRS. Hepatorenal syndrome was precipitated by spontaneous bacterial peritonitis 5(62.5%), upper gastrointestinal bleeding 2(25%) and unknown 1(12.5%). In Bivariate analysis total leucocyte count, Serum sodium, Model for End-stage Liver Disease – Sodium (MELD- Na), serum bilirubin and use of rifaximin were predictors of HRS. Only use of rifaximin was the predictor in multivariate analysis. Conclusion: Serum sodium, bilirubin and MELD Na are important predictors of the hepatorenal syndrome. Rifaximin use may be preventive for HRS.